Interpersonal problems across restrictive and binge-purge samples: Data from a community-based eating disorders clinic - Raykos, B.; McEvoy, Peter; Carter, O.; Fursland, A.; Nathan, P. (Pergamon, 2014)
Contemporary models of eating disorders suggest that interpersonal problems contribute to the maintenance of eating disorders. This study examined whether baseline interpersonal problems differed across eating disorder diagnoses and across eating disorder subtypes (“restrictors” vs. “binge-purge” patients) in a large clinical sample. Patients with a primary eating disorder diagnosis (N = 406) completed measures of interpersonal problems, eating disorder symptoms, and mood prior to treatment at a specialist eating disorder clinic. Across the sample, more severe eating disorder psychopathology was associated with significantly greater difficulty socializing. Anorexia Nervosa (AN) / restrictor patients reported significantly greater difficulty socializing than Bulimia Nervosa (BN) / binge-purge patients. AN patients reported significantly greater difficulty on a measure of competitiveness/assertiveness compared to BN and Eating Disorder Not Otherwise Specified patients. All findings were significant after controlling for comorbid depression and anxiety symptoms. Interpersonal problems appear to be unique risk factors for eating disorders. Specific interpersonal mechanisms include difficulties socializing and being assertive, which were most pronounced in AN patients. These findings provide potential avenues for enhancing interventions, such as adjunctive assertiveness training for AN.